2018
DOI: 10.1111/ejn.13940
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial alternating current stimulation modulates auditory temporal resolution in elderly people

Abstract: Recent research provides evidence for a functional role of brain oscillations for perception. For example, auditory temporal resolution seems to be linked to individual gamma frequency of auditory cortex. Individual gamma frequency not only correlates with performance in between-channel gap detection tasks but can be modulated via auditory transcranial alternating current stimulation. Modulation of individual gamma frequency is accompanied by an improvement in gap detection performance. Aging changes electroph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…46 Studies have also reported that tDCS and tACS can influence performance on gap detection tasks, a common marker of central (vs. peripheral) auditory function. 4750 Taken together, the available evidence suggests the potential for NIBS methods like tDCS to modulate central auditory processing. 51,52 Given that central auditory processing can be negatively impacted in several conditions (e.g., stroke, speech in noise difficulties, auditory processing disorder), this could reflect an untapped area of future translational research.…”
Section: Discussionmentioning
confidence: 98%
“…46 Studies have also reported that tDCS and tACS can influence performance on gap detection tasks, a common marker of central (vs. peripheral) auditory function. 4750 Taken together, the available evidence suggests the potential for NIBS methods like tDCS to modulate central auditory processing. 51,52 Given that central auditory processing can be negatively impacted in several conditions (e.g., stroke, speech in noise difficulties, auditory processing disorder), this could reflect an untapped area of future translational research.…”
Section: Discussionmentioning
confidence: 98%
“…Considering the involvement of cerebellar theta activity in extinction of conditioned eyeblink responses based on animal studies ( Wang et al, 2014 , 2019 ), future research could still benefit from exploring simpler fear conditioning paradigms with non-invasive brain stimulation in the theta range. Furthermore, future studies could benefit from using personalized protocols known to have enhanced precision and effectiveness in targeting specific brain oscillation patterns, compared to fixed stimulation frequencies ( Del Felice et al, 2019 ; Baltus et al, 2020 ; Ayanampudi et al, 2022 ). Such investigations may provide clearer insights into the potential modulatory effects of non-invasive brain stimulation on fear learning and deepen our understanding of fear regulation mechanisms, potentially contributing to future therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as neuromodulational techniques are increasingly used to change the state of the brain, the effect of neuromodulation on peak gamma frequencies was tested. However, the knowledge is still limited: Transcranial alternating current stimulation (tACS) was reported to increase IGF [4,83,84], whereas transcranial direct current stimulation (tDCS) did not modulate IGF [85][86][87]. In addition, non-invasive vagal nerve stimulation was shown to decrease IGF [88].…”
Section: Brain Statesmentioning
confidence: 99%